(untitled) (Fiep Bulletin - online, 2013)
To walk is ideal to work the cardiovascular function, the level of physical conditioning, it helps to lost weight and strengthens the muscles of the legs and buttock. It too reduces the blood pressure, the cholesterol levels in blood, the risks of sickness in heart, osteoporose, diabetes, stress, between other (SOUZA, 2001). The aim of research is analyse the effects of the walking about the functional autonomy of elder women registered in two PSF´s in Juazeiro do Norte city CE, in a time of twelve weeks. The sample was made by 11 (eleven) woman with age by 64,82 (+ 3,48). They had submitted to protocol of evaluation by AF do GDLAM , it formed of tests of walking ten mters (C10M), to lift from chair and move yourself by home (LCLC), to lift of the sat position (LPS) and to lift of the nose decubit position (LPDV). To analyse and classification of the data, it was compared descriptive statistic of average, standard deviating maximum and minimum. And to comparision between tests, the nonparametric and Wilconxon test. The distribuition was created in graphic and chart, and the used classifications will be creates in graphic and chart, and variables. The results before C10m 6,98 (+0,97), LPS 10,28 (+2,27), LCLC 37,53 (+4,03), VTC 19,11 (+4,08) et LPDV 3,50 (+0,95) and after twelven weeks C10m 6,88 (+1,01), LPS 8,77 (+1,89), LCLC 40,53 (+6,52), VTC 12,19 (+3,09) and LPDV 3,14 (+1,32). It concluded that the elder woman that practice walking, they showed small difference in functional autonomy after 3 (three) months of practicing and didn´t having meaning the estatistcs results.